„ÖKO-TEST” – źródło informacji o proekologicznych produktach - Zaremba-Warnke, Sabina (“ŐKO-TEST” – source of information about environmentally friendly products, 2008)
The article contains the analysis of accessibility on the Polish consumer products’ market of information about environmentally friendly products. The author states the lack of such information – it is very difficult for common consumer to find some. The German magazine “ÖKO-TEST” is presented as an example of a generally accessible source of information about products’ environmental features.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 106-113